Method of Recognition of Forms When Trying to Select Street Direction - Novak, Štefan; Kolenc, Jurij (Promet - Traffic&Transportation, 2012)
Roads are one of the main factors which influence roadtraffic safety. They influence the time of the realisation and thecosts of the transport itself by their technical and exploitationcharacteristics. The right selection of a street will highly affectthe costs of transport that can be reduced, and the speed ofrealisation that can be increased. The paper presents one of themethods of recognition of forms which is later on also tested onan example of selecting the type of the street. The aim of this paperwas to show the possibilities of using the recognition offorms in the traffic and transport system. This way of selectionand classification is needed when it is necesswy to decide fastabout the direction of movement, particularly in special circumstances.